Temporal analysis of the incidence of meningitis in the Tehran metropolitan area, 1999-2005 - Heidarnia Mohammadali; Asgari Freshteh; Esteghamati Abdolreza; Mosavi-Jarrahi Alireza; Mousavi-Jarrahi Yasamin; Goya Mohammadmehdi (BMC, 2009)
Abstract Objectives The aim of this study was to describe the temporal determinants of meningitis incidence in the population living in the Tehran metropolis. Methods All cases of meningitis reported to health districts throughout the Tehran metropolis from 1999 to 2005 were abstracted from patient files. Referral cases (patients who did not reside in the Tehran metropolis) were excluded. For each year, sex- and age-specific incidences were estimated. Temporality and its determinants were analyzed using Poisson regression. Results Age-specific incidence is highest among males younger than 5 years of age at 10.2 cases per 100,000 population per year. The lowest incidence was among females aged 30 to 40 years at 0.72 cases per 100,000 population per year, with an overall male-to-female incidence ratio of 2.1. The temporal analysis showed seasonality, with a higher risk of meningitis in spring at a rate ratio of 1.31 with a 95% confidence interval (CI) of 1.20 to 1.41 and in autumn (rate ratio = 1.16, 95% CI 1.06, 1.27). For periodicity, we found a peak of occurrence around the years 2000 and 2003. Conclusion The epidemiology of meningitis in Iran follows similar patterns of age, sex, and seasonality distribution as found in other countries and populations.